Doctrine and Politics in the Latin Biblical Poetry of Philip Melanchthon’s Silesian Disciples - Modlińska-Piekarz, Angelika (Odrodzenie i Reformacja w Polsce, 2018)
This article deals with selected works by Philip Melanchthon’s Silesian disciples who studied in Wittenberg in the years 1545–1560: Jacob Kuchler from Jelenia Góra (about 1526 – about 1572), Joannes Seckerwitz from Wrocław (about 1529 – about 1583), Thomas Mawer from Trzebiel (1536–1575), Caspar Pridmann from Głogów (1537–1598) and Laurentius Fabricius from Ruda (1539–1577). The article’s focus is on the doctrinal and political meaning of the works used as a tool in fighting the Catholic Church and in spreading Protestantism in the stormy era of the religious struggle waged in Silesia and in the entire territory of Central and Northern Europe. The texts analysed here also aimed to promote and spread Protestant doctrines and principles (sola gratia, solus Christus, sola fide, sola Scriptura, predestination, the repudiation of priesthood and celibacy) across the Empire, Poland, Prussia and Livonia.